Being a woman and being a marketer in the territory-place called the fair / Ser mulher e ser feirante no território-lugar chamado feira - Patricia Quirino Rocha; Maria Augusta Mundim Vargas (Universidade Estadual de Alagoas, 2020)
This article aims to understand the territorialities of women who"put tent" at the fair of the municipality of Euclides da Cunha, backwoods of Bahia. For this, we build our references by phenomenology in order to observe the experiences, practices and knowledge of women as marketers, using as research tools, field diary and interviews concomitant to deepen a research and literature review. It was possible to know the trajectories of the marketers and their territorialities, by which we identified similarities and differences that characterize their practices. Among them, we highlight the bonds of sociability that develop with the other marketers and customers, revealing that the ways of being and being at the fair go beyond buying and selling relationships.